Clinico-epidemiological study of leprosy in a tertiary care hospital of Eastern India - Agrawal, Nisha; Saha, Tirtha Raj; Barua, Jayanta Kumar; Banerjee, Gautam; Chatterjee, Kingshuk; Halder, Saswati; Samanta, Prabal (International Journal of Research in Dermatology, 2023)
Background: Accurate diagnosis of leprosy is of paramount importance, because delays and misdiagnosis are more common in non-endemic zones. It has a long incubation period, varied clinical presentations, and reaction states which can present in any point of lifetime, becoming more challenging for proper management of this enigmatous disease. Methods: This was conducted as an institution based cross- sectional study over a period of 12 months. 100 patients were selected. Inclusion and exclusion criteria were maintained. Data collected was checked, tabulated, statistically analysed and compared with existing literature. Results: In our study, majority, 49% belonged in age group of 41-60 yrs, only 6% were less than 20 years old. Male: female ratio was 3.34. 62% were from rural areas. Family history of Hansen was present in 5%. 6% had Histoid while 5% had pure neuritic representing least common subtypes. Most common occupations were Housewives (19%), shopkeepers (16%) and office workers (16%). 59% presented with hypoesthesia, 28% with fever. 59% belonged to borderline, 27% belonged to polar spectrum. Trophic ulcers were found in 20%, clawing of digits in 27%. Conclusions: Leprosy is still a pressing problem in our country. A considerable number of children and adolescents get affected indicating high rate of transmission in community. A comprehensive approach includes proper diagnosis, treatment, and identification of reaction patterns, prevention of disability and deformities, and implementation of rehabilitation measures.